2011
DOI: 10.1371/journal.pone.0028609
|View full text |Cite
|
Sign up to set email alerts
|

Eurasian Tree Sparrows, Risk for H5N1 Virus Spread and Human Contamination through Buddhist Ritual: An Experimental Approach

Abstract: BackgroundThe Highly Pathogenic Avian Influenza H5N1 virus has dramatically spread throughout Southeast Asia since its first detection in 1997. Merit Release Birds, such as the Eurasian Tree Sparrow, are believed to increase one's positive karma when kissed and released during Buddhist rituals. Since these birds are often in close contact with both poultry and humans, we investigated their potential role in the spread of H5N1 virus.Methodology/Principal FindingsSeven series of experiments were conducted in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Despite little shedding in the contacts, seroconversion of at least 1 contact animal in each of the finch and sparrow groups indicates exposure with antigenic epitopes of the subtype H7 hemagglutinin. The minimal transmission to direct contacts observed in our study is consistent with previous observations of avian influenza virus infection of songbirds ( 15 , 20 , 23 25 ). The parakeets in particular showed no contact animal shedding or seroconversion, a phenomenon we have previously observed with an A(H3N8) isolate from a songbird (R.G.…”
Section: Discussionsupporting
confidence: 93%
“…Despite little shedding in the contacts, seroconversion of at least 1 contact animal in each of the finch and sparrow groups indicates exposure with antigenic epitopes of the subtype H7 hemagglutinin. The minimal transmission to direct contacts observed in our study is consistent with previous observations of avian influenza virus infection of songbirds ( 15 , 20 , 23 25 ). The parakeets in particular showed no contact animal shedding or seroconversion, a phenomenon we have previously observed with an A(H3N8) isolate from a songbird (R.G.…”
Section: Discussionsupporting
confidence: 93%
“…Human cases of infection with A(H5N1) virus following direct exposure to dead wild birds were reported in Azerbaijan [29] and consuming uncooked duck blood has been suggested as a source of infection in some cases in Vietnam [30]. It has also been experimentally shown that small sparrows could theoretically be infected after contact with infected poultry and serological evidence of influenza contamination of these birds has been found in Cambodia [31]. …”
Section: Discussionmentioning
confidence: 99%
“…Three studies of HP H5N1 in tree sparrows also studied intraspecific and interspecific transmission. In one, directly inoculated sparrows were highly susceptible to the virus, with high viral loads and mortality, but no contact tree sparrows became infected [ 113 ]. However, contact transmission did occur to chickens, and more than one-half of sparrows exposed to infected ducks showed high levels of viral RNA on swabs taken from feathers.…”
Section: Passeriformes: Thrushes Finches Swallows Starlings Spmentioning
confidence: 99%